The influences of calcium fluoride and silica particles on improving color homogeneity of WLEDs - Anh-Minh D. Tran; Nguyen Doan Quoc Anh; Nguyen Thi Phuong Loan (Universitas Ahmad Dahlan, 2020)
The LEDs lighting device with phosphor ingredient (pcLEDs) is among the most common lighting methods in recent years and evaluated by chromatic uniformity and lighting capacity. Therefore, we introduce the phosphor particles that can improve the scattering efficiency (SEPs) to apply in pcLEDs at 8500 K correlated color temperature (CCT) with the expectation to produce better pcLEDs by enhancing both quantity and quality of emitted light. Combining various materials such as CaF2 and SiO2 with yellow Y3Al5O12:Ce3+ phosphor composition in the pcLEDs simulation created by the LightTools program is the mechanism of this research. The simulated pcLEDs are tested and the results will be verified with Mie-scattering theory. The observation of the simulation leads to the conclusion about the scattering coefficients of SEPs at 455 nm and 595 nm wavelengths. The calculation showed that CaF2 is better for color homogeneity yet suffer from luminous flux deficiency as the concentration gets higher. On the other hand, SiO2 is the scattering enhancement material that can maintain high luminous flux regardless of its concentration.